Palaeo-pollution from mining activities in the Vosges Mountains: 1000 years and still bioavailable. (July 2016) - Mariet, Anne-Lise; de Vaufleury, Annette; Bégeot, Carole; Walter-Simonnet, Anne-Véronique; Gimbert, Frédéric
Abstract: Mining and smelting activities have contaminated the environment with trace metals (TMs) at a worldwide scale for at least two millennia. A combination of chemical approaches and active biomonitoring was performed to analyse the environmental availability and bioavailability of TM palaeo-pollution in a former PbAg mining district in the Vosges Mountains, France. Along a soil TM contamination gradient that covered eight stations, including two archaeological mining sites, the toxicokinetics of six TMs (Pb, Cd, As, Ag, Co, Sb) in the snail Cantareus aspersus revealed that palaeo-pollution from the studied sites remains bioavailable. This study provides the first data on the accumulation kinetics of Ag and Co for C. aspersus . The environmental availability of the TMs was estimated with three chemical extraction methods ( aqua regia, EDTA 50 mM, CaCl2 10 mM). Univariate regression analyses showed that EDTA extraction is the best method for estimating the bioavailability of Pb, As, Ag, Co and Sb to snails. None of the three extractants was efficient for Cd. A multivariate analysis of bioaccumulation data revealed that TM bioavailability and transfer were modulated by exposure sources (soil, humus and vegetation) rather than by soil physico-chemical characteristics. Hence, although the deposition of mining wastes dates back several centuries, these wastes still represent a source of contamination that must be considered to develop relevant site management and environmental risk assessment. Graphical abstract: Highlights: Deposited several centuries ago, mine wastes still represent contamination sources. Cantareus aspersus snails were used as bioindicators in a biomonitoring campaign. Palaeo-pollution are still bioavailable to vegetation and snails. Bioavailability of trace metals to snails depends on exposure source. EDTA is the best extractant for evaluating trace metal bioavailability to snails. Abstract : Field exposure analysis of land snails highlights the bioavailability and transfer of TMs in soils contaminated by mining wastes deposited several centuries ago.